2022
DOI: 10.3390/ijerph19042140
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Biochar Amendment on Soil Properties and Organic Matter Composition in Trace Element-Contaminated Soil

Abstract: The application of biochar as an organic amendment in polluted soils can facilitate their recovery by reducing the availability of contaminants. In the present work, the effect of biochar application to acid soils contaminated by heavy metal spillage is studied to assess its effect on the quantity and composition of soil organic matter (SOM), with special attention given to soil humic acids (HAs). This effect is poorly known and of great importance, as HA is one of the most active components of SOM. The field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…These results indicate that the obtained pellets have the potential to be used as fertilizers or as additives to fertilizers and biostimulants. This is corroborated by the findings of other researchers, such as De la Rosa and colleagues, which demonstrate that biocarbon has a beneficial impact on soil properties, including a reduction in acidity and an enhancement in water retention capacity [139].…”
Section: Biostimulators In the Form Of Granulessupporting
confidence: 81%
“…These results indicate that the obtained pellets have the potential to be used as fertilizers or as additives to fertilizers and biostimulants. This is corroborated by the findings of other researchers, such as De la Rosa and colleagues, which demonstrate that biocarbon has a beneficial impact on soil properties, including a reduction in acidity and an enhancement in water retention capacity [139].…”
Section: Biostimulators In the Form Of Granulessupporting
confidence: 81%
“…The presence of isoprenoids (cis-2-Methyl-7-octadecene; hexahydrofarnesyl acetone) remained constant although a slight decrease was observed with time (Table 1). These compounds are probably rest of pigments side chains, mainly chlorophyll, frequently found in humic substances (de la Rosa et al, 2022). A significantly higher ISO abundance was detected under the tree canopy (1.13 ± 0.19 under the tree canopy; 0.61 ± 0.03 in open pasture, p = 0.000).…”
Section: Other Compoundsmentioning
confidence: 94%
“…Acidification of tailings soil can lead to the mobility of heavy metals and toxicity to plants increased, and lead to plant deficiency of P, Ca, K, Mg, and Mo (Dai et al, 2017). Many studies have reported a significant increase in soil pH after biochar application (De la Rosa et al, 2022). Aamer et al (2020) observed that 2% biochar application increased soil pH from 5.48 to 6.11.…”
Section: Soil Phmentioning
confidence: 99%